2021
DOI: 10.1038/s41467-021-26236-5
|View full text |Cite
|
Sign up to set email alerts
|

StemBond hydrogels control the mechanical microenvironment for pluripotent stem cells

Abstract: Studies of mechanical signalling are typically performed by comparing cells cultured on soft and stiff hydrogel-based substrates. However, it is challenging to independently and robustly control both substrate stiffness and extracellular matrix tethering to substrates, making matrix tethering a potentially confounding variable in mechanical signalling investigations. Moreover, unstable matrix tethering can lead to poor cell attachment and weak engagement of cell adhesions. To address this, we developed StemBon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 85 publications
2
19
0
Order By: Relevance
“…Here we used a microgel system to encapsulate embryonic stem cells into spherical 3D agarose scaffolds. Consistent with previous studies, we found the soft, non-degradable 3D matrix to be beneficial for pluripotency 21, 25, 50, 51 . The interpretation of RNA-seq data on microgel-encapsulated cells revealed Plakoglobin, a vertebrate homologue of β-catenin and a crucial factor for embryonic development, as one of the most differentially upregulated genes 52, 53 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Here we used a microgel system to encapsulate embryonic stem cells into spherical 3D agarose scaffolds. Consistent with previous studies, we found the soft, non-degradable 3D matrix to be beneficial for pluripotency 21, 25, 50, 51 . The interpretation of RNA-seq data on microgel-encapsulated cells revealed Plakoglobin, a vertebrate homologue of β-catenin and a crucial factor for embryonic development, as one of the most differentially upregulated genes 52, 53 .…”
Section: Discussionsupporting
confidence: 92%
“…Any two of the three 2i/LIF components (PD, CHIR and LIF) are sufficient to maintain naïve pluripotency 20 . In addition to chemical and cytokine-mediated signals, biomechanical cues are emerging key players in the regulation of embryonic [21][22][23][24][25] and adult stem cells 4,[26][27][28] . However, the identity of mechanoresponsive genes in ESCs and the mechanisms transforming physical responses into transcriptional programs remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of the above hydrogel stiffness affecting cell behavior, it may regulate cell expression by affecting the expression of related genes and proteins ( Labouesse et al, 2021 ). In human adipose-derived stem cells (hADSCs) encapsulated by methacrylated hyaluronan (MeHA) hydrogel, the contents of two cartilage-related gene aggrecans and type II collagen increased significantly with the increase of hydrogel stiffness.…”
Section: Effects Of Hydrogel Stiffness On Tissue Repairmentioning
confidence: 99%
“…Integrins form clusters, cause the conformation changes of mechanosensitive proteins like talin and vinculin, activate the mechanosensitive ion channels, and then activate the downstream transcription factor activity [ 120 ]. To construct an optimal mechanical microenvironment for culturing pluripotent stem cells, Chalut’s group modified PAAm hydrogel protocol by addition of 6-acrylamidohexanoic acid (AHA) as co-factor [ 121 ]. The carboxyl terminal groups of the AHA are covalently linked to extracellular matrix (ECM) protein through a carbodiimide reaction, and thus form stable ECM–substrate attachment.…”
Section: Biomaterials For Regulation Of Stem Cell Fatementioning
confidence: 99%